Subjective and objective skin colour of a farmworker group in the Limpopo Province, South Africa - Linde, Karlien; Wright, Caradee Yael; du Plessis, Johannes Lodewykus (Skin research and technology, 2020)
Background Farmworkers in the Limpopo Province, South Africa, are at risk of excessive exposure to solar ultraviolet radiation (sUVR) due to both their work and the sUVR environment in the geographic area. However, the natural protection provided by this group's skin against sUVR has not been quantified. The aim of this study was to evaluate the subjective and objective skin colour of a group of farmworkers in order to classify the natural photoprotection provided by melanin and to evaluate the different measurement methods. Materials and Methods Skin colour was established by using the subjective Fitzpatrick skin phototype system (FST) questionnaire and two objective methods, namely the individual typology angle (ITA°) and melanin index (MI). A total of 71 farmworkers participated in the study. Results Black Africans tended to perceive their skin to be lighter than objectively measured, potentially due to cultural factors. The constitutive skin colour of most farmworkers was objectively classified in the FST V/brown group. Significant differences were found between the ITA° and MI of sun‐exposed (constitutive) and non–sun‐exposed (facultative) skin in Black African and White farmworkers. A strong correlation was found between ITA° and MI on different anatomical positions indicating both methods are appropriate to determine skin colour in deeply pigmented skin. Conclusion The evaluation of skin colour with the use of both subjective and objective methods may be used to design an effective photoprotection programme for farmworkers in the Limpopo Province.